DETERMINANTS AND PRODUCTION EFFICIENCY OF COCOA FARMING IN MELAYA DISTRICT, JEMBRANA REGENCY - I Gusti Ngurah Bagus Ari Sanjaya; Ni Nyoman Yuliarmi (Adisam Publisher, 2025)
Cocoa is a leading plantation commodity in Indonesia that contributes to foreign exchange earnings. However, productivity in Bali Province—particularly in Melaya District, Jembrana Regency—remains low. This study aims to analyze the simultaneous and partial effects of land area, labor, capital, and the number of trees on cocoa production; evaluate input efficiency; and determine the production scale of cocoa farming in Melaya District, Jembrana Regency. The study employs a quantitative associative approach with a sample of cocoa farmers selected through proportionate stratified random sampling. Data were collected through observation and interviews. Data analysis was conducted using descriptive statistics, Cobb-Douglas regression, classical assumption tests, significance tests, input efficiency analysis, and economic scale determination. The results indicate that land area, labor, capital, and number of trees simultaneously have a significant effect on cocoa production. Partially, land area, labor, and capital have a positive and significant effect, while the number of trees does not have a significant positive effect on cocoa production. Efficiency analysis shows that land area, labor, and capital are still efficient and can be increased, while the number of trees is inefficient and should not be increased. The analysis of economic scale reveals that cocoa production in Melaya District is experiencing decreasing returns to scale. These findings imply the need for improvements in input management to sustainably increase productivity and the welfare of cocoa farmers.